Phenotypic Recovery of a Heterobasidion Isolate Infected by a Debilitation-Associated Virus Is Related to Altered Host Gene Expression and Reduced Virus Titer - Kashif, Muhammad; Jurvansuu, Jaana; Hyder, Rafiqul; Vainio, Eeva J.; Hantula, Jarkko (Frontiers in Microbiology, 2021)
The fungal genus Heterobasidion includes forest pathogenic species hosting a diverse group of partitiviruses. They include the host debilitating Heterobasidion partitivirus 13 strain an1 (HetPV13-an1), which was originally observed in a slowly growing H. annosum strain 94233. In this study, a relatively fast-growing sector strain 94233-RC3 was isolated from a highly debilitated mycelial culture of 94233, and its gene expression and virus transcript quantities as well as the genomic sequence of HetPV13-an1 were examined. The sequence of HetPV13-an1 genome in 94233-RC3 was identical to that in the original 94233, and thus not the reason for the partial phenotypic recovery. According to RNA-seq analysis, the HetPV13-an1 infected 94233-RC3 transcribed eight genes differently from the partitivirus-free 94233-32D. Three of these genes were downregulated and five upregulated. The number of differentially expressed genes was considerably lower and the changes in their expression were small compared to those of the highly debilitated original strain 94233 with the exception of the most highly upregulated ones, and therefore viral effects on the host transcriptome correlated with the degree of the virus-caused debilitation. The amounts of RdRp and CP transcripts of HetPV13-an1 were considerably lower in 94233-RC3 and also in 94233 strain infected by a closely related mildly debilitating virus HetPV13-an2, suggesting that the virus titer would have a role in determining the effect of HetPV13 viruses on their hosts.